Correlation Between Serum Soluble PD-1, CD8+ , CD4+ T Lymphocyte Counts and Liver Stiffness in Antiviral-Naïve Chronic Hepatitis B Patients - Rizki Aliana; Eddy Yuristo; Legiran Legiran; Imam Suprianto; Vidi Orba Busro; Muhamad Ayus Astoni; Anjab Akmal Sya'roni; Suyata Suyata; Samy Zaky (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2026)
Background: Chronic hepatitis B (CHB) disease is a major global health problem with a high burden in Asia, including Indonesia. Liver stiffness measurement by transient elastography is a non-invasive key tool to assess fibrosis severity. The immune response in CHB involves T cell exhaustion marked by elevated soluble PD-1 (sPD-1) and changes in T lymphocyte subsets, which may influence fibrosis progression. This study aimed to assess the correlation between serum sPD-1, CD4+, and CD8+ T lymphocyte counts and liver stiffness in antiviral-naïve CHB patients.Methods: A cross-sectional study was conducted among 60 untreated CHB patients at Mohammad Hoesin Hospital, Palembang, Indonesia. The sPD-1 was measured by ELISA, while CD4+ and CD8+ T cell counts were determined via flow cytometry. Liver stiffness was assessed by transient elastography. Spearman correlation and multivariate linear regression were used to analyze associations between immune markers and liver stiffness.Results: Serum sPD-1 showed a significant positive correlation with liver stiffness (r = 0.481, p 0.001), while CD8+ T lymphocyte count was negatively correlated (r = –0.553, p 0.001). CD4+ T lymphocyte count showed no significant bivariate correlation (r = –0.189, p = 0.149). In the multivariate analysis, sPD-1 (β = 0.050, p 0.001), CD4+ T cells (β = –0.018, p = 0.001), and AST (β = 0.061, p = 0.005) were independent predictors of liver stiffness.Conclusion: Serum sPD-1 and CD4+ T-lymphocyte count are independently associated with liver stiffness in antiviral-naïve CHB patients. These findings suggested the involvement of immune exhaustion and liver injury in HBV-related fibrosis.